Can the appropriate use of humour and anecdotes from practice improve the retention of information in nursing lectures and would stand-up comedy techniques aid lecturers?. (2nd May 2021) - Smith, Mike; Pringle, Alan
Abstract : This article discusses the use of humour and explores the impact of emotionally charged material used in nursing education, putting forward suggestions about the use of stand-up comedy techniques to enhance presentation skills. It further explores neurobiological evidence that may support these suggestions. As the landscape of nurse education is changing, the article discusses how larger class sizes, online delivery via virtual learning environments and other technology-enhanced learning methods may impact on how lessons are presented.